2021
DOI: 10.1111/cts.13075
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic variants of infliximab response in young patients with inflammatory bowel disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Consistent with our approach, other authors explored the association of the SNPs rs3936991 (FCGR3A) and rs1800629 (TNF) with response, serum trough levels, and ADA production in IBD patients treated with infliximab [101]. Curci et al showed that variant C rs396991 was associated with a poorer clinical response at the end of induction and at 22 and at 52 weeks of treatment with infliximab.…”
Section: Genetic Variantsmentioning
confidence: 85%
See 3 more Smart Citations
“…Consistent with our approach, other authors explored the association of the SNPs rs3936991 (FCGR3A) and rs1800629 (TNF) with response, serum trough levels, and ADA production in IBD patients treated with infliximab [101]. Curci et al showed that variant C rs396991 was associated with a poorer clinical response at the end of induction and at 22 and at 52 weeks of treatment with infliximab.…”
Section: Genetic Variantsmentioning
confidence: 85%
“…Curci et al showed that variant C rs396991 was associated with a poorer clinical response at the end of induction and at 22 and at 52 weeks of treatment with infliximab. In addition, patients with this variant had lower infliximab levels and were more likely to produce ADAs than patients with the wild-type genotype [101].…”
Section: Genetic Variantsmentioning
confidence: 97%
See 2 more Smart Citations
“…Other genetic polymorphisms, such as in the CXCL12, IL-10, and Fc gamma receptor (FCGR3A) genes, have also been proposed to be associated with a risk of ADAb formation to TNFi [67,[74][75][76]. Whilst an area of research interest, at present, there is no definitive evidence to support genetic testing to predict ADAb formation as most studies are limited by small patient numbers or a lack of replication.…”
Section: Genetic Factorsmentioning
confidence: 99%